Protocol for the implementation of a statewide mobile addiction program - Cynthia A Tschampl; Craig Regis; Nafissa E Johnson; Margot Trotter Davis; Dominic Hodgkin; Mary F Brolin; Elizabeth Do; Constance M Horgan; Traci C Green; Brittni Reilly; MaryKate Duska; Elsie M Taveras (Becaris Publishing Limited, 2023)
With overdose deaths increasing, improving access to harm reduction and low barrier substance use disorder treatment is more important than ever. The Community Care in Reach R model uses a mobile unit to bring both harm reduction and clinical care for addiction to people experiencing barriers to officebased care. These mobile units provide many resources and services to people who use drugs, including safer consumption supplies, naloxone,medication for substance use disorder treatment, and a wide range of primary and preventative care. This protocol outlines the evaluation plan for the Community in Care R model in MA, USA. Using the RE-AIM framework, this evaluation will assess how mobile services engage new and underserved communities in addiction services and primary and preventative care.